Integrasi Culturally Responsive Teaching dalam Pembelajaran Bahasa Inggris berbasis T-PACK - Yulia Sari Harahap; Nurhafni Siregar; Teguh Satria Amin (Journal on Education, 2024)
The aim of this study is to integrate CRT (Culturally Responsive Teaching) and TPACK in English language learning and develop 21st Century skills with a culturally responsive approach. The research was conducted using a qualitative descriptive approach, which looked at each student and background holistically. Research is done using a variety of learning methods such as Think pair share, internships, discussions, direct instruction and debates. The CRT research associates the concept of learning English with the cultural background as well as the characteristics of the student. Practical Implementation of this method includes technological mastery, pedagogic knowledge and learning content. Data analysis techniques use the techniques presented by Miles and Huberman, namely data reduction, data presentation, and verification and conclusion withdrawal. The results of this study are demonstrating the application of TPACK's integrated CRT in developing 21st century skills for students, this can be seen from the development of learning in understanding the concepts of text material that are based on local intelligence. Increased because of the ongoing learning in addition to conveying theory there are also practices without expressions that directly involve the culture of students. A culturally responsive integrated approach to learning is an approach that unifies the culture of students and is associated with English text so that students can understand what teachers are telling and learning seems meaningful.